BLOOD PRESSURE-LOWERING EFFICACY OF OLMESARTAN RELATIVE TO OTHER ANGIOTENSIN II RECEPTOR ANTAGONISTS: AN OVERVIEW OF RANDOMIZED CONTROLLED STUDIES - Faiez Zannad; Renaud Fay (Российский кардиологический журнал, 2010)
The aim of the present work was to review published studies, investigating the dose-related efficacy on blood pressure (BP) of olmesartan and of other commercially available angiotensin II type I receptor blockers (ARBs). Patient population comprised mild to moderate hypertensive adult patients. We selected studies with comparable design and dose ranges. Dose-effect relationship plots were fitted for diastolic (DBP) and systolic (SBP) BP to the simplified Emax model. We also examined controlled studies of olmesartan vs. other individual ARBs. Our overview was based on 7280 patients, of whom 5769 received an ARB, and 1511 received placebo. Except for losartan, the data fitted correctly to the Emax model, with correlation coefficients ranging from 0.77 to 0.99. BP-lowering efficacy defined as Emax was superior with olmesartan, (DBP/SBP, mmHg: -9,0/-12,4) when compared with candesartan (-6,7/-11,3), irbesartan (-6,5/-11,2), and valsartan (-6,3/-8,9). Head-to-head comparisons of olmesartan to each of the other ARBs used at per-label “recommended doses” support the finding of a greater BP-lowering effect of olmesartan. This overview suggests that clinically relevant differences in maximal efficacy, as well as in efficacy of per-label recommended doses can be evidenced among individual ARBs. Olmesartan efficacy was consistently at the highest end of the range of efficacy of ARBs studied.